Slash your retirement risk how to make your money last with a simple, safe, and secure investment plan - Cook, James Christopher 1971- (Career Press, 2017)
"When it comes to retirement investing, too much emphasis today is on investments returns, which often come at the expense of income dependability and peace of mind. Slash Your Retirement Risk redefines how to invest for retirement to maximize your reliable income and stabilize your financial future. Rather than the typical approach to portfolio management -- focusing on returns and ignoring dramatic market downswings that can decimate portfolios -- author Chris Cook shows investors how to create income reliability without sacrificing reasonable growth. Instead of chasing uncertain returns, Slash Your Retirement Risk's strategy will help ensure your retirement portfolio will capitalize on opportunities for growth while weathering the inevitable economic ups and downs. You will achieve reliable returns and suffer fewer sleepless nights worrying about whether your money will last as long as you do. Slash Your Retirement Risk is your step-by-step guide to create a retirement portfolio that will provide true financial peace of mind, one that features: The broad diversification essential in today's globally interconnected marketplace. A built-in ability to capitalize on market upswings to generate growth. Automatic protections against inevitable market downswings. An investing strategy that minimizes fees and costs to maximize portfolio gains."--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher; resource not viewed
Keywords: Retirement -- Planning; Finance, Personal; Retraite; Planification; BUSINESS & ECONOMICS; Personal Finance; Retirement Planning; BUSINESS & ECONOMICS; Finance; Retirement; Planning